The Ascendancy of Second-Generation Antipsychotics as Frontline Antimanic Agents. Issue 6 (December 2015) - Miller, Christopher J.; Li, Mingfei; Penfold, Robert B.; Lee, Austin F.; Smith, Eric G.; Nordberg, Samuel S.; Osser, David N.; Bajor, Laura; Zhang, Fang; Bauer, Mark S.
Abstract : Introduction: Knowledge of the factors affecting the adoption of new medications can enhance mental health care and guide quality improvement and policy development. Food and Drug Administration indications for treating bipolar disorder with several second-generation antipsychotics (SGAs) in the 2000s represent an opportunity to identify factors that impact the spread of a then-innovative treatment through a new population. Methods: Analysis of Department of Veterans Affairs administrative data identified the population of 170, 811 veterans diagnosed with bipolar disorder from 2003 to 2010. We analyzed time trends and predictors of antimanic choice (SGA vs other) among the 40, 512 outpatients with bipolar disorder who initiated their first VA outpatient antimanic prescription, using multinomial logistic regression in month-by-month analyses. We conducted classwise analyses and investigated prespecified predictors among specific agents. Results: In classwise analyses, SGAs supplanted lithium, valproate, and carbamazepine/oxcarbazepine as the most commonly initiated antimanics by 2007. Psychosis, but not other indices of severity, predicted SGA initiation. Demographic analyses did not identify substantial disparities in initiation of SGAs. Drug-specific analyses revealed some consideration of medical comorbidities in choosing among specific antimanic agents, although effect sizes were small. Most patients initiating an antimanic had received an antidepressant in the previous year. Discussion: Second-generation antipsychotics quickly became the frontline antimanic treatment for bipolar disorder, although antidepressants most commonly predated antimanic prescriptions. Second-generation antipsychotics were used for a broad range of patients rather than being restricted to a severely ill subpopulation. The modest association of antimanic choice with relevant medical comorbidities suggests that continued attention to quality prescribing practices is warranted.